2023
DOI: 10.1186/s40854-022-00411-z
|View full text |Cite
|
Sign up to set email alerts
|

Are life insurance futures a safe haven during COVID-19?

Abstract: This study aims to examine whether life insurance futures can serve as a hedge against the COVID-19 pandemic and whether they have the characteristics of a safe haven under the impact of the health shocks of the COVID-19 pandemic. We chose three life insurance stock futures in India and one in Taiwan as samples, including the market index of the two countries and the number of confirmed COVID-19 cases as sample variables. We used the growth rate of COVID-19 cases as the threshold variable, estimated the asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is a true that unpredictable things and good and bad times happen randomly; thus, it is really appropriate to extend the meaning of this sentence to insurance. The so-called "insurance" means that once a risk occurs, it will inevitably cause large or small personal financial losses, but it can be compensated through gathering the resource power (such as money) of everyone from insuring insurance [37]. If you have bought insurance, you can avoid risks and benefit from an agreement of insurance.…”
Section: Ltci and Its Related Application Issues For Developing Poten...mentioning
confidence: 99%
“…It is a true that unpredictable things and good and bad times happen randomly; thus, it is really appropriate to extend the meaning of this sentence to insurance. The so-called "insurance" means that once a risk occurs, it will inevitably cause large or small personal financial losses, but it can be compensated through gathering the resource power (such as money) of everyone from insuring insurance [37]. If you have bought insurance, you can avoid risks and benefit from an agreement of insurance.…”
Section: Ltci and Its Related Application Issues For Developing Poten...mentioning
confidence: 99%
“…[ 53 ] have also found that green bonds could be a safe haven, but noted that they were not as effective as hedging financial sectors. [ 54 ] have examined insurance companies in India and Taiwan to see if they were safe havens during COVID-19. They have found that insurance futures served as a safe haven for the markets in these two countries, which suffered from high rates of infection.…”
Section: Literature Reviewmentioning
confidence: 99%